2018
DOI: 10.1016/s0140-6736(18)31310-2
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol use and burden for 195 countries and territories, 1990–2016: a systematic analysis for the Global Burden of Disease Study 2016

Abstract: SummaryBackgroundAlcohol use is a leading risk factor for death and disability, but its overall association with health remains complex given the possible protective effects of moderate alcohol consumption on some conditions. With our comprehensive approach to health accounting within the Global Burden of Diseases, Injuries, and Risk Factors Study 2016, we generated improved estimates of alcohol use and alcohol-attributable deaths and disability-adjusted life-years (DALYs) for 195 locations from 1990 to 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
1,172
7
20

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,255 publications
(1,265 citation statements)
references
References 32 publications
24
1,172
7
20
Order By: Relevance
“…Alcohol consumption increases the risk of mortality and cancer, suggesting that policies to address alcohol consumption should be reviewed [3]. Europe has the highest alcohol consumption rate per habitant worldwide, and this value continues to increase [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption increases the risk of mortality and cancer, suggesting that policies to address alcohol consumption should be reviewed [3]. Europe has the highest alcohol consumption rate per habitant worldwide, and this value continues to increase [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol, actually ethanol (C 2 H 5 OH), is a psychoactive molecule ingested by 2.4 billion people globally 1. A central nervous system depressant, it exists naturally and can be produced in people’s homes.…”
mentioning
confidence: 99%
“…Any alcohol consumption confers health risks, including for a range of cancers,2 and any possible cardiovascular benefits are smaller than was previously understood 3. Alcohol harms users through intoxication, organ toxicity, and addiction, which cause an estimated 2.8 million deaths every year 1. In a recent systematic review and meta-analysis the Global Burden of Disease Alcohol Collaborators concluded that the “the level of alcohol consumption that minimised harm across health outcomes was zero.”1…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The continuing health harms of alcohol require action,1 and PHE has been prominent in promoting a range of effective interventions, including minimum unit pricing 2…”
mentioning
confidence: 99%